As capacidades dinâmicas como vetores da estratégia para clientes com potencial inadequado de negócios em instituições financeiras - Moura, Gustavo Edmar de Faria (2018)
The changes in the financial industry in the 21st century are occurring even more dynamically. Deregulation, financial innovation and automation are the main forces that affect the sector's performance (GIRARDONE et al, 2004). In this context, this study examines the most relevant concepts and theories regarding strategy, the recent evolution of the Brazilian financial industry and the issues related to customer profitability. From there, it investigates what would be the contributions of the dynamic capabilities in the strategies for the adaptation of the business potential in medium and large corporate clients of a financial institution. The concept of dynamic capabilities fits as it emphasizes the importance of internal and external business processes, recognizing the importance of critical resources and a good strategy (TEECE, 2014). The research is justified by the inexistence of scientific papers addressing the Dynamic Capabilities theory in financial institutions, conferring potential novelty, and contributing to the strategic management of the segment. The methodology, qualitative, was performed through the analysis of document content complemented by in-depth interviews undertaken with professionals from a financial institution that operates in the country. The results obtained point to the importance of brand (solidity), product and service portfolio, ethics and capillarity as important resources and competences in this sector and segment. It is also observed the existence of a profitability strategy, with a greater focus on clients with inadequate business potential and a need for greater process dynamism and product flexibility to capture opportunities from this more competitive environment.